2010
DOI: 10.1071/an09201
|View full text |Cite
|
Sign up to set email alerts
|

Urine distribution and grazing behaviour of female sheep and cattle grazing a steep New Zealand hill pasture

Abstract: Much of the nitrogen (N) excreted by grazing animals is within highly concentrated urine patches. The N that is not used by plants is likely to be lost through leaching, emitted as N gases or added to the soil organic N pool. The present study used custom-made global positioning system (GPS) and urine sensors on 20 non-lactating ewes and 20 non-lactating beef heifers grazing steep hill country to determine potential critical source areas for N loss to the environment. Bite counters on four sheep and five heife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 18 publications
1
45
0
1
Order By: Relevance
“…Urine volume is mainly influenced by water intake and the mineral load ingested by the animal (Selbie et al 2015), and can be high when the moisture content of the diet is high, or when the herbage leaves are wet with rain water or dew (Doak 1952). Urine volume can also vary as a response to coping with changes in ambient temperatures (Betteridge et al 2010a). Data for sheep urine volume and frequency are scarce, but typically individual sheep urine events range between 100 and 200 mL (Doak 1952;Haynes and Williams 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine volume is mainly influenced by water intake and the mineral load ingested by the animal (Selbie et al 2015), and can be high when the moisture content of the diet is high, or when the herbage leaves are wet with rain water or dew (Doak 1952). Urine volume can also vary as a response to coping with changes in ambient temperatures (Betteridge et al 2010a). Data for sheep urine volume and frequency are scarce, but typically individual sheep urine events range between 100 and 200 mL (Doak 1952;Haynes and Williams 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Daily sheep urine volume ranged from 0.5 to 3 L in Ledgard et al (2008) and the frequency of urination events has been reported to range between 13 and 20 times per day (Doak 1952;Betteridge et al 2010aBetteridge et al , 2010b.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of gathering areas for excretion by sheep and cows, there is a distinction between urination sites and defecation sites (Betteridge, 2010a). By knowing their relative areas and locations, the estimated mass of excreta can be used to support computer models for the prediction of CSAs and, therefore, nitrogen (N) emissions.…”
Section: Animal Nitrogen Emissionsmentioning
confidence: 99%
“…This would contribute to a mitigation strategy related to N emissions arising from grazing livestock, especially if mitigations are targeted at CSAs (Betteridge et al 2011). The N losses are mainly in the form of gaseous losses to the atmosphere and leaching into the groundwater (Betteridge et al 2010a). Farmers require information on N losses in order to reduce emissions to meet local and international N leaching and greenhouse gas target levels.…”
Section: Animal Nitrogen Emissionsmentioning
confidence: 99%
See 1 more Smart Citation